Docetaxel-induced neuropathy: A pharmacogenetic case-control study of 150 women with early-stage breast cancer. (April 2015) - Eckhoff, Lise; Feddersen, Søren; Knoop, Ann S.; Ewertz, Marianne; Bergmann, Troels K.
Abstract: Background. Docetaxel is a highly effective treatment of a wide range of malignancies but is often associated with peripheral neuropathy. The genetic variability of genes involved in the transportation or metabolism of docetaxel may be responsible for the variation in docetaxel-induced peripheral neuropathy (DIPN). The main purpose of this study was to investigate the impact of genetic variants in GSTP1 and ABCB1 on DIPN. Material and methods. DNA was extracted from whole blood from 150 patients with early-stage breast cancer who had received adjuvant docetaxel from February 2011 to May 2012. Two polymorphisms in GSTP1 and three in ABCB1 were selected for the primary analysis, and a host of other candidate genes was explored and compared between 75 patients with clinician-reported DIPN grade ≥ 2 and 75 patients without DIPN. Results. Patients with the genetic variants GSTP1 rs1138272 C/T or T/T (114Ala/114Val or 114Val/114Val) genotype had an adjusted odds ratio of 3.82; 95% confidence interval 1.34–11.09 of developing DIPN. This result was confirmed in both analysis of cumulated docetaxel dose and haplotype analysis. None of the explorative genes investigated were significantly correlated with DIPN. Patients with a BMI ≥ 30 were five-fold more likely to have DIPN than patients with BMI < 25. Conclusion. We found that GSTP1 Ala114Val polymorphism is associated with occurrence of DIPN. This supports the theory that oxidative stress is involved in DIPN pathophysiology. If confirmed, this may be helpful in the risk assessment of DIPN and perhaps help to achieve better management of neurotoxicity.